Factors Associated with International Humanitarian Aid Appeal: Analysis of Disasters from 1995 to 2015 - Cheng, Lenard; Hertelendy, Attila; Hart, Alexander; Law, Lawrence; Hata, Ryan; Nouaime, Georgina; Issa, Fadi; Echeverri, Lina; Voskanyan, Amalia; Ciottone, Gregory (Prehospital and disaster medicine, 2023)
Introduction:International humanitarian aid is crucial in disasters but must be needs-driven and coordinated with requests from local authorities. We identify disaster and population factors associated with international aid appeal during disasters and hence guide preparation by international humanitarian aid providers.Method:In this retrospective database analysis, we searched the Emergency Events Database for all disasters from 1995 to 2015. Disasters with and without international aid appeals were compared by location, duration, type of disaster, deaths, number of people affected, and total estimated damage. Logistic regression was used to examine the association of each factor with international aid appeal.Results:Of 13,961 disasters recorded from 1995 to 2015, 168 (1.2%) involved international aid appeals. Aid appeals were more likely to be triggered by disasters which killed more people (OR 1.29 [95% confidence interval (CI) 1.02-1.64] log10 persons), affected more people (OR 1.85 [95%CI 1.57-2.18] / log10 persons), and occurred in Africa (OR 1.67 [95%CI 1.06-2.62). Earthquakes (OR 4.07 [95%CI 2.16-7.67]), volcanic activity (OR 6.23 [95%CI 2.50-15.53]), and insect infestations (OR 12.14 [95%CI 3.05-48.35]) were more likely to trigger international aid appeals. International aid appeals were less likely to be triggered by disasters which occurred in Asia (OR 0.46 [95%CI 0.29-0.73]) and which were transport accidents (OR 0.12 [95%CI 0.02-0.89]).Conclusion:International aid appeal during disasters was associated with greater magnitude of damage, disasters in Africa, and specific types of disasters such as earthquakes, volcanic activity, and insect infestations. Humanitarian aid providers can focus preparation on these identified factors.